Pendampingan Pengolahan Limbah Serabut Kelapa menjadi Cocofiber dan Cocopeat di Desa Manggar Raya - Saleh Hidayat; Meli Astriani; Wulandari Saputri; Nita Nuraini (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Manggar Raya Village is one of the villages located in Tanjung Lago District, Banyuasin Regency, South Sumatra Province. Manggar Raya village is one of the largest coconut producers. Still, the community only uses fruit flesh and coconut water to sell, while the coconut fiber is left as waste by the village community. Collaborative Service Activities with independent real-life college students aim to assist in the manual processing of coconut coir waste into cocofiber and cocopeat. Methods: Participants in the activity consisted of 21 residents of Manggar Raya Village. The participatory method used in community service assistance which includes the provision of material, practice, discussion and evaluation. Result: Positive response from activity participants. Participants were satisfied with the activities and learned about the waste management provided. Conclusion: Assistance in processing coconut fiber to the community can increase knowledge by 85% about how to process coconut fiber into cocofiber and cocopeat. In addition, participants gained the skills to make decorative pots from coconut fibers to increase the selling value of cocofiber. In the future, it is hoped that the people of Manggar Raya village can become the center of the coconut fiber processing industry in South Sumatra.